DT2008: A Promising New Genetic Resource for Improved Drought Tolerance in Soybean When Solely Dependent on Symbiotic N2 Fixation. (5th January 2015) - Sulieman, Saad; Ha, Chien Van; Nasr Esfahani, Maryam; Watanabe, Yasuko; Nishiyama, Rie; Pham, Chung Thi Bao; Nguyen, Dong Van; Tran, Lam-Son Phan
Abstract : Water deficit is one of the major constraints for soybean production in Vietnam. The soybean breeding research efforts conducted at the Agriculture Genetics Institute (AGI) of Vietnam resulted in the development of promising soybean genotypes, suitable for the drought-stressed areas in Vietnam and other countries. Such a variety, namely, DT2008, was recommended by AGI and widely used throughout the country. The aim of this work was to assess the growth of shoots, roots, and nodules of DT2008 versus Williams 82 (W82) in response to drought and subsequent rehydration in symbiotic association as a means to provide genetic resources for genomic research. Better shoot, root, and nodule growth and development were observed in the cultivar DT2008 under sufficient, water deficit, and recovery conditions. Our results represent a good foundation for further comparison of DT2008 and W82 at molecular levels using high throughput omic technologies, which will provide huge amounts of data, enabling us to understand the genetic network involved in regulation of soybean responses to water deficit and increasing the chances of developing drought-tolerant cultivars.